Functional Deficits Precede Structural Lesions in Mice With High-Fat Diet–Induced Diabetic Retinopathy - Rajagopal, Rithwick (Diabetes, 2016)
Obesity predisposes to human type 2 diabetes, the most common cause of diabetic retinopathy. To determine if high-fat diet–induced diabetes in mice can model retinal disease, we weaned mice to chow or a high-fat diet and tested the hypothesis that diet-induced metabolic disease promotes retinopathy. Compared with controls, mice fed a diet providing 42% of energy as fat developed obesity-related glucose intolerance by 6 months. There was no evidence of microvascular disease until 12 months, when trypsin digests and dye leakage assays showed high fat–fed mice had greater atrophic capillaries, pericyte ghosts, and permeability than controls. However, electroretinographic dysfunction began at 6 months in high fat–fed mice, manifested by increased latencies and reduced amplitudes of oscillatory potentials compared with controls. These electroretinographic abnormalities were correlated with glucose intolerance. Unexpectedly, retinas from high fat–fed mice manifested striking induction of stress kinase and neural inflammasome activation at 3 months, before the development of systemic glucose intolerance, electroretinographic defects, or microvascular disease. These results suggest that retinal disease in the diabetic milieu may progress through inflammatory and neuroretinal stages long before the development of vascular lesions representing the classic hallmark of diabetic retinopathy, establishing a model for assessing novel interventions to treat eye disease.